RETRACTED: Removal of Total Petroleum Hydrocarbon (TPH) crude oil by consortium bacteria acetobacter tropicalis and lactobacillus casei - Azzahra F.; Rinanti A.; Hadisoebroto Rositayanti; Minarti A.; Aphirta S.; Rahmiyati L.; Mahrendra S.M.P.; Sunaryo T. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001